The analysis of algorithm for cutting stock problem - Pokštas, Jonas; Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2023)
The analysis of heuristic algorithm for solving two dimensional cutting stock problem is presented in this paper.
Keywords: combinatorial optimization; two dimensional cutting stock problem; heuristic algorithm